Hand Gesture and Voice Assistants - Latha B.; Sowndarya Sri; K Swethamalya; Raghuwanshi Ashish; Feruza Rakhmatova; Kumar G. Sathish (E3S Web of Conferences, 2023)
Hand gesture mouse control for systems has received a lot of attention in recent years Because of its many uses and capability to efficiently connect with machines via human- computer interaction, hand gesture mouse control for systems has attracted a lot of attention in recent years. Most visual hand motion detection systems can only be used in specific settings due to the effects of lighting and complicated backgrounds. Together with the quick advancement of computer vision and machine learning, the need for human- machine interaction is also rising. Despite the complicated history, the suggested methodology provides a straightforward but efficient way to perform rapid manual tracking. In addition to hand tracking and gesture detection, this system also eliminates motion blur. The detected gesture is transformed into particular functional inputs, such clicking and mouse movement, to control other programmes. The project's voice assistant feature is one of its additional features. The voice assistants can be instructed verbally or by text. Voice-based intelligent assistants need an activating word, sometimes referred to as a wake word, before the command may be given.